1995
DOI: 10.1515/jpme.1995.23.3.149
|View full text |Cite
|
Sign up to set email alerts
|

Review article

Abstract: Literature concerning early genetic amniocentesis, obtained before 14-15 weeks of gestation, has been examined and compared. Key figures of post-procedural spontaneous fetal losses have been compared as well as cytogenetic data from the published series. Cytogenetically more samples fail to grow in the early weeks, but the diagnostic accuracy seems to be comparable with that of amniocentesis obtained in the later weeks. A sampling method, improving the cell yield by means of filtration, has been developed in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Only the amniotic (inner) sac should be aspirated, because the outer sac does not contain sufficient numbers of living fetal cells. Sundberg 1995 reviewed observational studies of early amniocentesis and found 12 published series with more than 100 pregnancies per study (5242 pregnancies in total). Unintended pregnancy loss varied between 1.9% and 4.7%, and laboratory failure varied between 0% and 20%.…”
Section: Introductionmentioning
confidence: 99%
“…Only the amniotic (inner) sac should be aspirated, because the outer sac does not contain sufficient numbers of living fetal cells. Sundberg 1995 reviewed observational studies of early amniocentesis and found 12 published series with more than 100 pregnancies per study (5242 pregnancies in total). Unintended pregnancy loss varied between 1.9% and 4.7%, and laboratory failure varied between 0% and 20%.…”
Section: Introductionmentioning
confidence: 99%